Engineering students’ judgments on the favorable effect that the class context has on their academic learning - Guadalupe Elizabeth Morales-Martinez; Maria Isolde Hedlefs-Aguilar; Ricardo Jesus Villarreal-Lozano; Maria Guadalupe Santos-Alcantara (Institute of Advanced Engineering and Science, 2022)
The COVID-19 pandemic has impacted human life, including educational settings. In Mexico, teachers and students found it necessary to adopt the online modality at all levels. As a result, both students and teachers face new demands and a re-conceptualization of their everyday academic lives. This study explored the engineering students' perception of the favorable effect level that the class context has on their learning. There were 551 participants took a cognitive algebra study. The experimental task involved reading 12 scenarios that described hypothetical online or face-to-face learning situations; then, each participant judged the degree to which these types of situations favor their learning, using an 11-point scale. The results indicated three cognitive styles when judging the degree to which each class context favors the learning. These styles share a similar cognitive mechanism in terms of information integration; however, the selection process and valuation of the factors differed across the groups. The students' perception on the class context influences their involvement and motivation level for courses on which they are enrolled. The present study's findings suggest that the cognitive algebra approach helps diagnose students' cognitive and emotional approach styles for different class contexts and provides information about the nature of their cognitive processes in terms of how students' judgments and attitudes towards classes are generated.